Tinjauan Filosofis Dan Teoritis Penggunaan Hukum Acara HIR/RBG Dalam Penyelesaian Sengketa Waris Di Pengadilan Agama - -, Domiri (UI Scholars Hub, 2016)
Act of the Republic of Indonesia, Number 7 Year 1989, Chapter 54 states that· the general procedural law in Religious Courts is HIRIRBG. HIRIRBG is sourced from western civil law, so that in resolving all matters which are under its authority, Religious Courts conducted general procedural law of HIRIRBG sourced from western civil law, including in resolving inheritance disputes. Therefore, the procedural law of inheritance in Religious Courts which the material law sourced from islamic law would be equated with the western civil law which its material law was sourced from european law in resolving disputes. However, the material law of islamic inheritance is totally different from the material law of western civil law. Based on above discussion, there would be some research questions such as: (1) why could the Religious Court conduct the procedural law sourced from western civil law instead of procedural law sourced from islamic law in resolving the islamic inheritance disputes?, (2) How to use general procedural law of HIRIRBG in resolving inheritance disputes at the Religious Courts seen from law system? Based on the historical approach, it can be concluded that the reasons why HIRIRBG is used for resolving inheritance disputes in the Religious Courts are: first, because the Dutch colonial government policies dicriminate Islam religion. Secondly, because the Dutch colonial government policy in the field of law, they made unification and codification of law. According to the law system · theory, the use of HIRIRBG in·resolving inheritance disputes at the Religious Courts is less appropriate because it is not compatible with legal system components such as the substance of the law, the legal structure and legal culture.